KONTRIBUSI KECERDASAN VISUAL SPASIAL DAN KECERDASAN LOGIS MATEMATIS TERHADAP PRESTASI BELAJAR GEOMETRI - Yandika Nugraha (Jurnal Pemikiran dan Penelitian Pendidikan Matematika (JP3M), 2018)
This study aims to determine the contribution of visual spatial intelligence and mathematical logical intelligence to geometry learning achievement in terms of student sex differences in the Tadris Mathematics Study Program at FTK UIN Mataram. The population of this study were all students of the Tadris Mathematics in the 5th semester who had taken geometry courses. Data was collected by documents of geometry courses and tests of mathematical logical intelligence and spatial visual intelligence. The results showed that simultaneously or partially it was known that mathematical logical intelligence, spatial visual intelligence, and gender influence the learning outcomes of geometry. Regression models obtained are Geometry Learning Results (Y) = 20,150+ 8.146 * Gender + 0.254 * K_Logis + 0.386 * K_Spasial.